Self-reported infertility and longitudinal measures of cardiovascular risk factors: The CARDIA study - Catherine Kim; Duke Appiah; Zhe Yin; Pamela J. Schreiner; Cora E. Lewis; Megan M. McLaughlin; Adrienne N. Dula; David S. Siscovick; Heather Huddleston (PLoS ONE, 2025)
Introduction Previous reports have noted associations between infertility in women and increased risk of cardiovascular disease (CVD) events in later life. However, reports conflict regarding the associations between infertility and CVD risk factors. Using data from a population-based cohort of Black and White women, we examined the association between longitudinal assessments of CVD risk factors and infertility. Methods The Coronary Artery Risk Development in Young Adults (CARDIA) study is a prospective cohort of Black and White women who have undergone repeated assessment of CVD risk factors beginning at study baseline (1985–1986). Risk factors included cigarette smoking, body mass index (BMI), blood pressure, lipid levels, glucose, and C-reactive protein. At approximately 40 years of age, an ancillary study assessed histories of infertility. We used generalized estimating equations with a logit link model to examine associations between infertility (dependent variable) and repeated CVD risk factors (independent variables), with adjustment for age, race, center, and education level in 1107 women. Results Cigarette use and higher levels of BMI, glucose, and triglycerides and lower levels of high-density lipoprotein cholesterol (HDL) were associated with infertility after adjustment for age, race, and education. Cigarette use had the strongest associations with self-reported infertility in multivariable models (odds ratio 1.85, 95% confidence interval 1.64, 2.14). Conclusions Women with infertility histories have adverse CVD risk factors across the reproductive lifespan, but cigarette use is the primary CVD risk factor for women’s self-reported infertility.